PEMBATALAN PERATURAN KEBIJAKSANAAN YANG DIBUAT BERDASARKAN ASAS FREIES ERMESSEN - Anak Agung Ayu Ari Widhyasari (Jurnal Aktual Justice, 2020)
The existence of policy regulations cannot be separated from the free authority (vrije bevoegdheid) of the government which is known as freies ermessen. The granting of freies ermessen to the government or state administration is actually a logical consequence of the concept of the welfare state, but within the framework of a rule of law, freies ermessen cannot be used indefinitely. This paper aims to determine the limits of the use of policy regulations in government administration and the forms of accountability when there are legal deviations. With the normative juridical method, this research concludes that the policy regulations taken by the government in an urgent situation must be limited by the signs of the General Principles of Good Governance (AAUPB) and if the policy regulations are formed without heeding these principles, the policy regulation can be canceled. .